Pengaruh Health Consciousness dan Nutritional Knowledge terhadap Purchase Intention dengan Brand Attitude sebagai Mediasi pada Ultra Milk Low Fat High Calcium - Nurrahim, Muhammad Fakhri; Listiana, Erna; Setiawan, Harry; Pebrianti, Wenny; Purmono, Bintoro Bagus (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
High consumer health awareness and nutritional knowledge have not always been followed by strong purchasing decisions. This study aims to analyze the influence of health consciousness and nutritional knowledge on purchase intention, with brand attitude as a mediating variable, among Ultra Milk Low Fat High Calcium consumers in Indonesia. This study used a quantitative approach with a causal associative research design. Data were collected through an online survey using a five-point Likert-scale questionnaire from 170 respondents who met the research criteria. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The results showed that health consciousness and nutritional knowledge significantly influenced brand attitude and purchase intention. In addition, brand attitude was proven to have a significant effect on purchase intention and acted as a mediating variable in the relationship between health consciousness and nutritional knowledge on purchase intention. These findings indicate that the formation of a positive attitude towards a brand is an important mechanism in converting consumer health awareness and nutritional knowledge into purchase intention. This research provides a theoretical contribution to the development of consumer behavior literature in the context of healthy beverage products, specifically low-fat, high-calcium UHT milk.